Type 2 Diabetes Patients' Perspectives, Experiences, and Barriers Toward Diabetes-Related Self-Care: A Qualitative Study From Pakistan - Bukhsh, Allah; Goh, Bey-Hing; Zimbudzi, Edward; Lo, Clement; Zoungas, Sophia; Chan, Kok-Gan; Khan, Tahir Mehmood (Frontiers in Endocrinology, 2020)
Objective: This study aimed to qualitatively explore perspectives, practices, and barriers to self-care practices (eating habits, physical activity, self-monitoring of blood glucose, and medicine intake behavior) in urban Pakistani adults with type 2 diabetes mellitus (T2DM). Methods: Pakistani adults with T2DM were recruited from the outpatient departments of two hospitals in Lahore. Semistructured interviews were conducted and audiorecorded until thematic saturation was reached. Two researchers thematically analyzed the data independently using NVivo® software with differences resolved by a third researcher. Results: Thirty-two Pakistani adults (aged 35–75 years, 62% female) participated in the study. Six themes were identified from qualitative analysis: role of family and friends, role of doctors and healthcare, patients' understanding about diabetes, complication of diabetes and other comorbidities, burden of self care, and life circumstances. A variable experience was observed with education and healthcare. Counseling by healthcare providers, family support, and fear of diabetes-associated complications are the key enablers that encourage study participants to adhere to diabetes-related self-care practices. Major barriers to self care are financial constraints, physical limitations, extreme weather conditions, social gatherings, loving food, forgetfulness, needle phobia, and a hectic job. Conclusion: Respondents identified many barriers to diabetes self care, particularly related to life situations and diabetes knowledge. Family support and education by healthcare providers were key influencers to self-care practices among Pakistani people with diabetes.